The Mechanical Theater and the Theater Crisis (Móin-Móin Magazine - Studies in the Art of Puppetry, 2024)
Jacques Copeau, in his text on the evolution of cinema and its impact on theater, expresses concerns about the growing influence of cinema, especially with the introduction of talking films, which he considers a threat to theater. He acknowledges cinema as a young and developing art form, highlighting the work of Charlie Chaplin. Copeau argues that cinema, by competing with theater, may lead to its crisis, but he also believes that this crisis can result in the purification and elevation of theater. He advocates for the need for structural reform in theater to face these challenges and promote artistic distinction.
Keywords: Jacques Copeau; french theater; cinema; mechanical theater; Charlie Chaplin